2015
DOI: 10.1159/000371404
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Lip/Palate, Short Stature, and Developmental Delay in a Boy with a 5.6-Mb Interstitial Deletion Involving 10p15.3p14

Abstract: The chromosome interval 10p15.3p14 harbors about a dozen genes. This region has been implicated in a few well-known human phenotypes, namely HDR syndrome (hypoparathyroidism, sensorineural deafness, and renal dysplasia) and DGS2 (DiGeorge syndrome 2), but a number of variable phenotypes have also been reported. Cleft lip/palate seems to be a very unusual finding within the clinical spectrum of patients with this deletion. Here, we report a male child born with short stature, cleft lip/palate, and feeding probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Submicroscopic deletion of 10p15.3 is mainly related to cognitive deficits, speech disorders, motor delay, and hypotonia with a deleted region from 0.15 to 4 Mb ( 21 ). However, Gamba et al reported a male child with a 5.6 Mb deletion at 10p15.3–10p14 who exhibited short stature, cleft lip/palate, and feeding problems ( 23 ). In view of the aforementioned studies, the microdeletion of 10p15.3 was inferred to give rise to different features and is seemingly not related to the deletion size.…”
Section: Discussionmentioning
confidence: 99%
“…Submicroscopic deletion of 10p15.3 is mainly related to cognitive deficits, speech disorders, motor delay, and hypotonia with a deleted region from 0.15 to 4 Mb ( 21 ). However, Gamba et al reported a male child with a 5.6 Mb deletion at 10p15.3–10p14 who exhibited short stature, cleft lip/palate, and feeding problems ( 23 ). In view of the aforementioned studies, the microdeletion of 10p15.3 was inferred to give rise to different features and is seemingly not related to the deletion size.…”
Section: Discussionmentioning
confidence: 99%